Defeating epilepsy: A global public health commitment. Issue 2 (22nd March 2017) - Saxena, Shekhar; Li, Shichuo
Summary: This article points out that defeating epilepsy is a global public health commitment and a new challenge. This is because: epilepsy causes a heavy burden and very high treatment gap; in the field of life sciences and medicine, the 21st century would be the "Century of Brain Science"; a number of national brain research initiatives provide a great opportunity to reveal the secret of epilepsy; the Global Campaign against Epilepsy and the Mental Health Gap Action Programme made great contributions in the epilepsy control work worldwide; the historical WHA68.20 resolution gives great strength to promote defeating epilepsy.